ANALISIS IMPLEMENTASI PERATURAN DAERAH NOMOR 05 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH DI KECAMATAN BARONG TONGKOK KABUPATEN KUTAI BARAT - Doltianus .; Masjaya .; Rita Kalalinggi (Jurnal Administrative Reform, 2017)
The purpose of this study is to describe and analyze the implementation of the Regional Regulation No. 05 of 2013 About Waste Management. Analysis of the data used is Interactive Model developed by Miles, Huberman and Saldana. The research showed that the implementation of West Kutai Regional Regulation No. 05 of 2013 on Waste Management in Barong Tongkok District has been done according to the rules. But application of the rules was less effective in managing waste. This was evidence by garbages strewn in various places, such as streets, public places or in landfills while.